Multi-color polymer pen lithography for oligonucleotide arrays. Issue 83 (29th September 2016) - Kumar, R.; Weigel, S.; Meyer, R.; Niemeyer, C. M.; Fuchs, H.; Hirtz, M.
Abstract : Multi-color patterning by polymer pen lithography (PPL) was used to fabricate covalently immobilized fluorophore and oligonucleotide arrays with up to five different components. These can easily be translated for presentation of multiple protein types to a single cell. Abstract : Multi-color patterning by polymer pen lithography (PPL) was used to fabricate covalently immobilized fluorophore and oligonucleotide arrays with up to five different components. The oligonucleotide arrays offer a virtually unlimited inventory of orthogonal binding tags for self-assembly of proteins as demonstrated by use of the arrays to monitor cell-protein interactions of MCF7 cells.